Nursing care of a case of juvenile myopia treated by electric plum-blossom needle (电梅花针叩刺法治疗1例青少年近视的护理体会) - SONG Yanfang (宋延芳); WANG Xiao (王潇); CHANG Mingsi (常明思) (中西医结合护理)
This paper summarized and analyzed the clinical efficacy of electric plum-blossom needle tapping and needling in the treatment of 1 case of juvenile mild myopia. Under the guidance of Traditional Chinese Medicine syndrome differentiation and nursing theory, electric plum-blossom needle tapping and needling was adopted. Interventions such as nutrition support and psychological care were carried out during the treatment, in order to improve the recovery of the patient with juvenile myopia. (本文总结1例采用电梅花针治疗轻度近视患者的护理经验, 基于中医辨证施护理论, 针对性取穴, 采取电梅花针叩刺治疗, 同时配合饮食、情志等护理措施, 能有效改善患儿视力。)